2022
DOI: 10.3389/fpsyg.2021.773913
|View full text |Cite
|
Sign up to set email alerts
|

German Laypeople’s Willingness to Donate Toward Insect Conservation: Application of an Extended Protection Motivation Theory

Abstract: It is essential to engage the public in conservation measures to conserve insects. We investigate the Protection Motivation Theory (PMT), as well as knowledge, attitudes, and sociodemographic variables (gender, age, education level, and income) as predictors of willingness to donate (WTD) and actual donations to insect conservation for a representative German sample (N = 515; MAge = 49.36, SD = 16.73; female = 50.1%). The PMT subcomponents severity, self-efficacy, and response efficacy, as well as attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…While the TPB originally included attitudes toward a specific behavior (e.g., donating toward insect conservation), previous research also found that attitudes toward a being or an object (e.g. insects) can predict intentions and behavior (Dörge et al, 2022). Dörge et al (2022) found that attitude toward insects was the most important factor influencing the WTD to an insect conservation project.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the TPB originally included attitudes toward a specific behavior (e.g., donating toward insect conservation), previous research also found that attitudes toward a being or an object (e.g. insects) can predict intentions and behavior (Dörge et al, 2022). Dörge et al (2022) found that attitude toward insects was the most important factor influencing the WTD to an insect conservation project.…”
Section: Introductionmentioning
confidence: 99%
“…insects) can predict intentions and behavior (Dörge et al, 2022). Dörge et al (2022) found that attitude toward insects was the most important factor influencing the WTD to an insect conservation project. Moreover, the WTD had a positive influence on the actual donation; thus, investigating the attitudes and their influence on the WTD can be useful for NGOs and campaign development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One method researchers have employed to investigate the relationship between attitudes toward conservation and biodiversity is the willingness-to-pay (WTP) procedure ( Martín-López et al, 2007 ; Tsi et al, 2008 ; Wang and Jia, 2012 ; Echeverri et al, 2017 ; Dörge et al, 2022 ). The WTP procedure when used to study attitudes toward animals assumes that people will pay for the conservation of an animal according to their perceptions of that animal’s worth, typically in the form of a monetary donation to support conservation.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to underline potential differences between paradigms that measure intended versus actual donations to animal conservation. For example, in Germany Dörge et al (2022) measured both intended and actual donations to insects. Though all respondents were favorable toward insect conservation, a significant intention-behavior gap was found in their response patterns, where their intentions to donate to insect conservation were larger than their actual donations.…”
Section: Introductionmentioning
confidence: 99%